Spirituality-Based Character Education Strategic Management - Henderikus Dasrimin; Ali Imron; Achmad Supriyanto (Jurnal Pendidikan Humaniora, 2019)
Abstract: The purpose of this study is to determine the process of strategic management of character-based characterization of Carmelite spirituality at Senior High School. This study uses a qualitative ap-proach with multi-site study design. Data were collected through observation, interviews and documentation studies. Data analysis used single data analysis and cross-site data analysis. The results of the study show that: (1) strategic planning is characterized by the formation of organizational structures and task descriptions by principals, (2) character education programs formulated in Academic Guidebooks or Learning Guidelines (3) the implementation of character education is done by assigning character values in the spirit of prayer, brotherhood, and service, (4) evaluation is carried out regularly, while monitoring is carried out throughout the whole process of character education.Key Words: strategic management, character education, karmel spiritualityAbstrak: Tujuan penelitian ini untuk mengetahui proses manajemen strategis pendidikan karakter ber-basis spiritualitas Karmel di Sekolah Menengah Atas. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi multi situs. Data dikumpulkan melalui observasi, wawancara, dan studi dokumentasi. Analisis data menggunakan analisis data tunggal dan analisis data lintas situs. Hasil penelitian menunjuk-kan bahwa: (1) perencanaan strategis ditandai dengan pembentukan struktur organisai dan deskripsi tugas oleh kepala sekolah, (2) program pendidikan karakter diformulasikan dalam Buku Panduan Akademik atau Buku Pedoman Pembelajaran (3) pelaksanaan pendidikan karakter dilakukan dengan mempresentasi-kan nilai-nilai karakter dalam semangat doa, persaudaraan, dan pelayanan, (4) evaluasi dilaksanakan se-cara berkala, sedangkan monitoring dilakukan pada seluruh proses pendidikan karakter.Kata kunci: manajemen strategis, pendidikan karakter, spiritualitas karmel